THE EFFECT OF USING THE OMETV APPLICATION ON THE SPEAKING ACHIEVEMENT OF 11TH- GRADE STUDENTS AT SMK MARISI MEDAN - Nelinda Kristauli Nasution; Febrina S.L Lumbantobing; Christina Natalina Saragi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to investigate the effect of using the OmeTV application on the speaking achievement of 11th-grade students at SMK Marisi Medan. Speaking is one of the most essential skills in English learning; however, many students face difficulties such as limited vocabulary, lack of fluency, poor pronunciation, and low confidence. To address these issues, OmeTV a video chat platform that connects users worldwide in real-time conversations was used as a learning medium to provide authentic and interactive speaking practice. This study employed a quantitative experimental design using the pre-test and post-test control group method. The population consisted of eleventh-grade students of SMK Marisi Medan, with a total sample of 55 students divided into an experimental group and a control group.